2012
DOI: 10.1136/annrheumdis-2012-201451
|View full text |Cite
|
Sign up to set email alerts
|

An increased rate of falling leads to a rise in fracture risk in postmenopausal women with self-reported osteoarthritis: a prospective multinational cohort study (GLOW)

Abstract: Objective Patients with osteoarthritis have increased bone mass, but no decrease in fractures. We studied the association between self-reported osteoarthritis and incident falls and fractures in postmenopausal women. Methods GLOW is a prospective, multinational cohort of 60 393 non-institutionalised women aged ≥55 years who had visited primary care practices within the previous 2 years. Questionnaires were mailed at yearly intervals. Patients were classified as osteoarthritic if they answered yes to the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 35 publications
4
82
0
2
Order By: Relevance
“…Our results showing higher fall risk in patients with KOA with an objective technique is compatible with several previous studies highlighting the high incidence of falls in these patients (17)(18)(19). OA has been reported to be associated with an increased risk of falling, with fall rates up to 50% of individuals with OA, compared to 30% of healthy older adults (1).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showing higher fall risk in patients with KOA with an objective technique is compatible with several previous studies highlighting the high incidence of falls in these patients (17)(18)(19). OA has been reported to be associated with an increased risk of falling, with fall rates up to 50% of individuals with OA, compared to 30% of healthy older adults (1).…”
Section: Discussionsupporting
confidence: 92%
“…It has long been speculated that this may relate to an increased risk of falls in OA cases, 50 and indeed a recent large prospective study supported this hypothesis, showing that an association between (selfreported) OA and fracture was largely attenuated by adjusting for incident falls. 51 Finally, and intriguingly, longitudinal studies have suggested that, in contrast to incident OA, progression of pre-existing OA may be inversely related to BMD. This finding was particularly striking in a paper by Zhang et al 17 studying the Framingham population, in whom a clear association between increasing age-specific femoral neck BMD quartiles and reduced risk of knee OA progression over the 8-year study period was seen.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 99%
“…The information recorded includes demographic information, clinical diagnoses (International Classification of Diseases 10th revision [ICD-10]), hospital referrals, laboratory tests and treatments (drug dispensed in community pharmacies). GPs meeting predefined standards of quality were allowed to contribute to the SIDIAP [21] database, providing reliable clinical data for biomedical research [23,24]. The quality of these data has been previously documented [21][22][23][24], and SIDIAP has been widely used to study the epidemiology of a number of health outcomes including osteoporotic fractures [23].…”
Section: Study Design and Sources Of Datamentioning
confidence: 99%